Tapering-pressure VAC therapy for wound exudation in POPF after pancreatoduodenectomy: a single-center experience - Liu, Guo-Hua; Xu, Zhen-Yue; Tan, Jian-Hui; Li, Jia-xing; Xu, Jun-Er; Tan, Xiao-Yu; Zhai, Jing-Wei; Wu, Jia-yuan; Zhong, Guo-Hui; Li, Ming-Yi (Frontiers in Surgery, 2025)
BackgroundPancreaticoduodenectomy(PD) is the only effective treatment for the peri-ampullar carcinoma. However, postoperative pancreatic fistula(POPF) is the most intractable complication causing relevant mortality. Moreover, pancreatic juice may exude from the wound that would lead to more serious complications. Tapering pressure of wall vacuum-assisted closure (VAC) therapy is considered one of the best treatment to wound exudation. Here, we report on a single center series of 5 POPF cases accompanying wound exudation following open or Laparoscopic-assisted pancreatoduodenectomy, successfully managed by VAC.MethodsWe enrolled all patients who experienced POPF ensuing wound exudation following open or Laparoscopic-assisted pancreatoduodenectomy (OPD or LAPD) and received tapering pressure of vacuum-assisted closure (VAC) therapy between July 2017 and August 2024. For VAC, we utilized wall suction device devised by our center applying the technique of negative pressure wound therapy(NPWT). And we adjusted the tapering pressure of the abdominal wound wall vacuum which fixed to a 8Fr or 12Fr suction catheter and connected to the pressure regulator between −50 and −100 mmHg according to the wound exudation amount. When the amount of the wound exudation were less than 100 ml, the wall vacuum suction catheter could be connected to the negative pressure balloon so that the patients could be able to get out of bed. The wall vacuum of VAC was removed when the pancreatic fistula had sufficiently healed which resulting in complete wound healing.ResultsA total of 60 patients underwent OPD or LAPD. Among them, 9 had occured clinically related pancreatic fistulaI(CR-POPF)according to International Study Group on Pancreatic Fistula grade (POPF; 30%). one of the 3 grade C patients underwent Re-laparotomy due to the completely separated pancreaticojejunostomy and postoperative hemorrhage. 5 of the 6 grade B patients was performed tapering pressure of wall vacuum-assisted closure therapy for pancreatic juice exudation from the wound, and all of these patients had good outcomes by this VAC therapy.ConclusionTapering pressure of wall VAC therapy could be a safe and effective treatment in the management of POPF ensuing wound exudation following open or Laparoscopic-assisted pancreatoduodenectomy. And this therapy may potentially reduce POPF-associated mortality.